Asymmetric information, dynamic debt issuance, and the term structure of credit spreads - Luca Benzoni; Lorenzo Garlappi; Robert S. Goldstein (Federal Reserve Bank of Chicago, 2019)
We propose a tractable model of a firm's dynamic debt and equity issuance policies in the presence of asymmetric information. Because "investment-grade" firms can access debt markets, managers who observe a bad private signal can both conceal this information and shield shareholders from infusing capital into the firm by issuing new debt to service existing debt, thus avoiding default. The implication is that the "asymmetric information channel" can generate jumps to default (from the creditors' perspective) only for those "high-yield" firms that have exhausted their ability to borrow. Thus, our model deepens the "credit spread puzzle" for investment-grade firms.
Keywords: G12; G32; G33; 330; Credit spreads; Capital structure; Corporate Default; Jumps to Default